1993
DOI: 10.1177/019874299301800402
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cross-Age Tutoring on the Academic Achievement, Social Behaviors, and Self-Perceptions of Low-Achieving African-American Males with Behavioral Disorders

Abstract: Four low-achieving fifth-grade African-American males with behavioral disorders tutored sight words to four low-achieving second-grade African-American males with behavioral disorders. Four fifth-grade and four second-grade African-American males with behavioral disorders who did not participate in the tutoring program served as comparisons for the tutors and tutees. The effects of the tutoring program on social behaviors was assessed through direct observations and pre/post ratings by classroom teachers. Simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 8 publications
2
59
0
Order By: Relevance
“…The students involved in the current study were identified as having significant behavioral problems and had been receiving special education services for a number of years. In the few studies that have measured achievement and behavioral measures (e.g., Cochran, Feng, Cartledge, & Hamilton, 1993), limited effects have been reported. Thus, the degree to which improved social behavior is related to effective reading interventions with this population of students is still unclear.…”
Section: About the Authorsmentioning
confidence: 99%
“…The students involved in the current study were identified as having significant behavioral problems and had been receiving special education services for a number of years. In the few studies that have measured achievement and behavioral measures (e.g., Cochran, Feng, Cartledge, & Hamilton, 1993), limited effects have been reported. Thus, the degree to which improved social behavior is related to effective reading interventions with this population of students is still unclear.…”
Section: About the Authorsmentioning
confidence: 99%
“…However, Gardner et al (2001) contend that this type of improvement is consistent with the results reported by other researchers, all of whom noted that participation in structured after-school programs and implementation of peer-mediated interventions can have important benefits (e.g., improved academic and social progress) for urban at-risk students (Cochran et al, 1993;Greenwood et al, 1989;Halpern, 1992;Marshall et al, 1997;Posner & Vandell, 1994; as reported in Gardner et al, 2001). …”
Section: The Mt Olivet After-school Programsupporting
confidence: 61%
“…I found that throughout the literature (Beck, 1999;Cochran et al, 1993;Gardner, et al, 2001;Greenwood et al, 1999;Halpern, 1999) there is unanimous agreement that the most effective means of assisting at-risk Black students today is through the establishment of well-thought-out after-school programs and partnership initiatives. Therefore, one of the things I did in my literature review was to compare the effectiveness of the various programs presented therein with the program model at the Overtown Youth Center, which as I stated previously, claims to be having great success in empowering the youth there and in encouraging them to develop a love and respect for education and for giving back to their community.…”
Section: Review Of the Studymentioning
confidence: 99%
“…Peer-mediated interventions studies have shown that students can effectively help improve the social behaviors of their peers (e.g., Arreaga-Mayer, 1998;Cochran, Feng, Cartledge, & Hamilton, 1993;Mortweet, 1996;Sideridis et al. 1997).…”
Section: Interventionsmentioning
confidence: 99%